Caste matters - Yengde, Suraj
"In this explosive book, Suraj Yengde, a first-generation Dalit scholar educated across continents, challenges deep-seated beliefs about caste and unpacks its many layers. He describes his gut-wrenching experiences of growing up in a Dalit basti, the multiple humiliations suffered by Dalits on a daily basis, and their incredible resilience enabled by love and humour. As he brings to light the immovable glass ceiling that exists for Dalits even in politics, bureaucracy and judiciary, Yengde provides an unflinchingly honest account of divisions within the Dalit community itself-from their internal caste divisions to the conduct of elite Dalits and their tokenized forms of modern-day untouchability-all operating under the inescapable influences of Brahminical doctrines. This path-breaking book reveals how caste crushes human creativity and is disturbingly similar to other forms of oppression, such as race, class and gender. At once a reflection on inequality and a call to arms, Caste Matters argues that until Dalits lay claim to power and Brahmins join hands against Brahminism to effect real transformation, caste will continue to matter." -- Book jacket.
Introduction : caste souls: motifs of the twenty-first century -- Being a dalit -- Neo-dalit rising -- The many shades of dalits -- The dalit middle class -- Dalit capitalism -- Brahmins against Brahminism.
Includes bibliographical references (pages 301-325).
Keywords: Dalits -- India; Dalits -- India; Caste-based discrimination -- India; Caste-based discrimination; Dalits; Dalits